An experimental study on the evaluation of temperature uniformity on the surface of a blackbody using infrared cameras. Issue 3 (27th May 2022) - Yoon, S.T.; Park, J.C.; Cho, Y.J.
ABSTRACT: Blackbody radiation is standardised electromagnetic energy emitted into space at a given temperature and wavelength distribution. It is used as a reference model to compare radiation emitted from various objects. This reference performance of blackbody systems should be maintained through periodic inspection and calibration. In this study, temperature uniformity on the surface of the blackbody was evaluated using infrared cameras. To this end, we divided the blackbody system measurements into 'before' and 'after' calibration sets and examined the blackbody surface in different bands, using two infrared cameras with different measurement principles. To evaluate surface temperature uniformity, we calculated the signal transfer function, equivalent noise temperature difference, and 3D noise of the infrared detector, and then comparatively analysed them.